Recurrent uterine inflammatory myofibroblastic tumor previously managed as leiomyosarcoma has sustained response to alectinib - Erica V. Carballo; Tra V. Pham; Gulisa Turashvili; Krisztina Hanley; Kristen D. Starbuck; Jane L. Meisel (Elsevier, 2022)
Soft tissue sarcomas encompass a wide range of histologic subtypes with varied clinical implications. The incorporation of comprehensive genetic profiling into clinical practice is refining our ability to make these distinctions in diagnosis to better reflect prognosis and clinical behavior of a tumor. In this report, we describe a case of recurrent inflammatory myofibroblastic tumor (IMT) of the uterus, initially diagnosed and managed as leiomyosarcoma. At the time of recurrence, the patient was found to have a TNS1-ALK rearrangement and was treated successfully with alectinib, a second-generation anaplastic lymphoma kinase (ALK)-inhibitor. She had a complete response by imaging six months after initiation of alectinib and remains without evidence of disease at 36 months follow-up. Pathology review in the setting of her known ALK fusion and the 2020 update to the World Health Organization Classification of Female Genital Tumors led to a change in diagnosis from leiomyosarcoma to IMT. Our case highlights the role of molecular testing in the diagnosis and management of uterine mesenchymal tumors and the efficacy of alectinib in this ALK-rearranged recurrent IMT of the uterus. Care must be taken to differentiate between IMT and other uterine mesenchymal tumors as this distinction can impact prognosis and management. Furthermore, this case adds to the growing body of evidence supporting the paradigm shift toward developing molecularly targeted therapies rather than disease site-specific treatments, especially in cases of recurrence as recommended by the National Comprehensive Cancer Network.